Emerging Roles of MicroRNA in the Embryo–Endometrium Cross Talk - Dior, Uri P.; Kogan, Liron; Chill, Henry H.; Eizenberg, Neta; Simon, Alexander; Revel, Ariel (Seminars in Reproductive Medicine, 2014)
Embryo implantation requires a reciprocal interaction between the blastocyst and endometrium and is associated with complex regulatory mechanisms. Since their discovery, microRNAs have become prominent regulatory candidates, providing missing links for many biological pathways. In recent years, microRNAs have been implicated as one of the important players in the regulation of multiple physiological functions of the endometrium. This review aims to present recent knowledge pertaining to the diverse aspects of microRNAs in the embryo–endometrial cross talk. We will focus on the role of microRNAs in decidualization. Next, we will review recent studies investigating the role of microRNAs in recurrent pregnancy loss. Finally, we will discuss the role of microRNAs in the tissue invasion of implantation and compare that with tissue invasion in cancers.
Keywords: microRNA; endometrium; implantation; decidualization; recurrent pregnancy loss